As memórias do que aconteceu: religiosidade, tecnologias e traduções nos meios populares - José Rogério Lopes; André Luiz da Silva; Régis de Toledo Souza (Ciências Sociais Unisinos)
The article discusses ethnographic references of a project that investigates how the use of audiovisual recording technologies allows lower classes subjects objectify themselves in religious manifestations, producing reflexivities on various events and their religious- ness. The analysis of these references considers two possibilities of objectification: the resulting projections of the subjects on goods and objects, unveiled since the interaction processes laid down in religious events, and another on the way designed for the goods and objects, that extrapolate their relational values when moving mediations that operate to objectifications in another order of interactions, or produce hybridisms between orders of different interactions. Based on questions raised at the Feast of the Círio de Nazaré and in other ethnographic accounts, it becomes clear how the uses of such technologies relativize the registers of memory and events among subjects who participate in religious events.